ISAK NUMBER 35 : NON-PROFIT ORGANIZATION IN FINANCIAL REPORTING - Nurasik Nurasik; Bernika Ivanda Zulfi Lestari; Sarwenda Biduri; Wiwit Hariyanto (International Journal of Business, Law and Political Science, 2024)
This study aims to determine the suitability of the financial statements presented by the Al Falah Mosque Foundation in Surabaya with the Interpretation of Financial Accounting Standards (ISAK) Number 35 concerning Presentation of Financial Statements of Non-Profit Oriented Entities. This research uses qualitative research with an interpretive approach. Data collection techniques through interviews, observation and documentation. The results obtained from this research are that Based on the results and discussion of research conducted by researchers, it can be concluded that, the financial statements of the Al Falah Mosque Foundation Surabaya have been presented in accordance with ISAK 35, namely concerning the Presentation of Financial Statements of Non-Profit Oriented Entities and prepared in accordance with Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). This can be seen from the financial statements that have been presented by the AL Falah Surabaya Mosque Foundation have fulfilled the elements of ISAK 35, namely: (1) The statement of financial position has been classified into several sections, namely current assets and non-current assets, liabilities and net assets; (2) The comprehensive income report has been classified in accordance with its restrictions, namely unbound and temporarily bound, it's just that there is a difference in the mention of terms in the comprehensive income report into an activity report; (3) The report on changes in net assets is made into 1 (one) with activity reports; (4) The cash flow statement is prepared using the direct method; and (5) Notes to the financial statements of Masjid Al Falah Foundation do not record the receipt of endowments and grants that have been received. The financial statements of the Al Falah Mosque Foundation Surabaya are only intended for the internal foundation, namely to the Trustees, unless the foundation has a loan at the bank, the financial statements are also reported to the bank.